Evolving images in juvenile justice: Cues to corrections’ future - Reed, Thomas E. (American journal of criminal justice, 1980)
Three late 19th century images of delinquents helped to shape the early juvenile justice system. These were images of juveniles as immature, nonpersons; biological inferiority and associated danger; and medically sick and infectious. An appropriate response was a juvenile system predicated upon confined, paternalistic treatment. This paper assumes that changes in these images provide cues to the future shape of juvenile corrections. These changes included recognition that dangerous is rare and unpredictable; that normalcy is more descriptive of delinquency than is sickness; and that the legally defined image of juveniles has shifted from nonpersons and chattel to persons and citizens. Appropriate responses to these images include community corrections, alienation reduction, and the right to treatment and responsibility.